A solution-processed zero-dimensional all-inorganic perovskite scintillator for high resolution gamma-ray spectroscopy detection. Issue 17 (23rd April 2020) - Xu, Qiang; Wang, Juan; Shao, Wenyi; Ouyang, Xiao; Wang, Xiang; Zhang, Xinlei; Guo, Yong; Ouyang, Xiaoping
Abstract : A zero-dimensional all-inorganic CsPbBr3 nanocrystal embedded Cs4 PbBr6 scintillator has been achieved. Owing to the low dimensional quantum effect, this all-inorganic scintillator exhibits desirable scintillation performance. Abstract : Low dimensional scintillators have been successfully and widely applied in the radiation-detection community for home security, scientific research, and imaging. We have grown zero-dimensional Cs4 PbBr6 materials with CsPbBr3 nanocrystals embedded by using a solution-growth method at low temperature. We have demonstrated the scintillation properties of these 0D nanoscintillators with high luminescence quantum efficiency for green light. In addition, we have successfully achieved pulse height spectra with this 0D perovskite material, which has been demonstrated with fast decay time (<10 ns), high energy resolution (3.0 ± 0.1%, 59.5 keV from 241 Am), high light yield (64 000 photons per MeV) and long term stability under various atmospheres (moisture, radiation). These results are much better than those of the most widely used commercial products such as NaI(Tl). It also demonstrates that this 0D all-inorganic material can be employed as a scintillator for ionization radiation applications such as X-ray imaging and spectroscopy applications.